Effect of Cooling Rate on the Microstructure of Al-Zn Alloys with Addition of Silicon as Nanocomposite - S. García-Villarreal; A. Arizmendi-Morquecho; A. Chávez-Valdez; J. A. Aguilar-Martínez; M. A. Esneider-Alcalá; L. Falcón-Franco (Advances in Materials Science and Engineering)
Al-43.5Zn-1.5Si (wt%) alloys are widely used as coatings on steel substrates. This kind of coatings is manufactured by hot-dip process, in which Si is added as solid particles or master alloy. The role of Si during formation of the coating is to control the metallurgical reactions between solid steel and liquid Al-Zn-Si alloy initially forming an AlZnFeSi intermetallic layer and next the excess of Si forms intermetallic compounds, which grows over this alloy layer, segregates into the Zn rich interdendritic regions, and solidifies as eutectic reaction product as massive particles with needle like morphology. Therefore, during the experimental procedure is very difficult to control the final morphology and distribution of the silicon phase. The acicular morphology of this phase greatly affects the mechanical properties of the alloy because it acts as stress concentrators. When the coated steel sheet is subjected to bending, the coating presents huge cracks due to the presence of silicon phase. Therefore, the aim of the paper was to propose a new methodology to control the silicon phase through its addition to Al-Zn alloy as nanocomposite and additionally determine the effect of cooling rate (between 10 and 50°Cs−1) on the solidification microstructure and mechanical properties of Al-Zn alloy.